2018
DOI: 10.1111/sjtg.12244
|View full text |Cite
|
Sign up to set email alerts
|

Shifting approaches to slums in Chennai: Political coalitions, policy discourses and practices

Abstract: Slums pose a persistent challenge for fast growing urban areas in the global South, despite several decades of policy intervention. While Chennai has adopted several strategies ranging from upgrading to reconstruction, the city has been unable to deliver its target of 'clearing' slum settlements. Through an analysis of four enumeration reports and a look at the evolving political contexts and subsequent practices, we illustrate the evolution of slum policy approaches in Chennai since the 1970s. The analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
(49 reference statements)
1
14
0
Order By: Relevance
“…Material processes, finances and institutions set limits and constraints. The city as a nexus of powerful networks is also constrained by actors’ mandates, which apply only within administrative boundaries, meaning that relations between cities and their surrounding areas are not easily integrated (Saharan et al., 2018).…”
Section: Situating the Configuration Concept Within Current Debatesmentioning
confidence: 99%
“…Material processes, finances and institutions set limits and constraints. The city as a nexus of powerful networks is also constrained by actors’ mandates, which apply only within administrative boundaries, meaning that relations between cities and their surrounding areas are not easily integrated (Saharan et al., 2018).…”
Section: Situating the Configuration Concept Within Current Debatesmentioning
confidence: 99%
“…The SCS is supported by the World Bank's Madras Urban Development Project (MUDP) that covers the improvements of 434 slums [56,57]. In some cases, however, safer cities can be the result of slums' clearance like the Maspero Triangle informal area in downtown Cairo, Egypt (2018).…”
Section: Urban Clearance As a Strategy For Upgradingmentioning
confidence: 99%
“…While these studies contribute to knowledge and management of slums, a critical review of the extant literature reveals a lack of a clear policy framework for slum governance. The phenomenon is largely due to the absence of a strong policy agenda for slums (Marx et al , 2013), and divisions among institutions for the management of slums (Kusters et al , 2018; Malik et al , 2021; Saharan et al , 2018). While the above research has indicated pointers accounting for a void in slum governance, the issue of a policy framework for slum governance is missing, leaving a gap in the literature.…”
Section: Introductionmentioning
confidence: 99%